IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE MATHEMATICS TEACHERS (ResearchJet Journal of Analysis and Inventions, 2021)
It can be seen from this article that a lot of effective work is being done to improve the methodological training of future mathematicians, which is becoming a problem today.